Autoantibodies in patients with bronchial carcinoma. Issue 4 (August 1975) - Hodson, M E; Turner-Warwick, M
Abstract : No overall increase in the incidence of antinuclear, smooth muscle or reticulin antibodies was observed in a group of 105 patients with bronchial carcinoma of various classified histological types. Smooth muscle antibody was, however, demonstrated in 27% of patients with undifferentiated carcinoma compared to 5% of controls (P less than 0-05). A highly significant increase in antinuclear antibodies in patients with adenocarcinoma was found (31% compared with 5% of controls--P less than 0-01). There as no apparent correlation between the presence of these antibodies and age, sex or other clinical features studied. A detailed study of the reproducibility of the antibody results, studied by indirect immunofluorescence in patients with bronchial carcinoma, is reported.